Faktor Penentu Keberhasilan Manajemen E-learning dan Minat Belajar Mahasiswa : (Studi kasus mahasiswa FTI Universitas Sebelas April Sumedang) - Leni Nurhayati; Reny Rian Marliana; Sri Bekti Handayani Ningsih; Iyat Ratna K (Pusat Riset dan Inovasi Nasional, 2024)
Along with the development of the digital era, the use of e-Learning has become inevitable. Almost all countries in the world, including Indonesia, are implementing e-learning in the world of education. However, to be able to implement e-learning successfully, there are several determining factors for success that must be met. The determining factors for the success of implementing e-learning cannot be separated from how management is carried out by an institution in implementing learning using e-learning. The success of e-learning implementation is also influenced by the level of user satisfaction. The successful implementation of e-learning can also influence students' interest in learning. The aim of this research is to determine the factors determining the success of e-learning implementation and their influence on students' interest in learning. The research method used is quantitative research. The conclusion obtained from the results of this research is that there are 2 factors that determine success in implementing e-learning, management of the content development process and management of the e-learning environment. E-learning environment management has a significant influence on four constructs of student learning interest, namely involvement, interest, acceptance and feelings of enjoyment. And management of the content development process has a significant effect on acceptance and feelings of enjoyment. So the research results show that E-Learning Environment management has a significant effect on interest in learning, while Content Development Process management for buying gas only has a significant effect on aspects of acceptance and feelings of pleasure.